Pengaruh Sosial Media Marketing, Electronic Word Of Mouth ( Ewom ) , Dan Konten Marketing Terhadap Keputusan Pembelian Skincare Skintific ( Studi Kasus Pada Mahasiswa FEB Unisma Angkatan 2021 ) - Al Amin, Rintan Anastasya; Priyono, Achmad Agus; Arsyianto, Muhammad Tody (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study investigates the impact of social media marketing, electronic word of mouth (eWOM), and content marketing on purchasing decisions for Skintific skincare products among students at the Islamic University of Malang, class of 2021. Using a quantitative approach with a survey method, 60 respondents were selected through non-probability sampling with the snowball technique. Data were collected via questionnaires and analyzed using multiple linear regression. The results show that while all three variables significantly influence purchasing decisions simultaneously, only content marketing has a significant partial effect, whereas social media marketing and eWOM do not. These findings highlight content marketing as the key factor driving consumer purchasing behavior for Skintific. Therefore, companies should focus on optimizing content marketing strategies to enhance product appeal and consumer interest. Keywords: Social media marketing, Electronic Word Of Mouth (eWOM), Content marketing, Purchasing decisions, Skintific skincare